Eccrine spiradenoma: an uncommon breast tumour - Norly, S; Ros’aini, P; Lim, HC (Department of Surgery, UKM Medical Centre, 2012)
Eccrine spiradenoma is a benign tumour of the sweat gland. Eccrine glands can be found almost everywhere but are mostly concentrated on the palms, soles and the axillae. Lesions involving the breast are rare. We present a case of a 13-years-old Malay girl with eccrine spiradenoma of the breast. The clinical presentation and histological features are being described.